Manajemen Perencanaan Pendidikan Islam Di Madrasah Ibtidaiyah Salafiyah Karangjompo - ISTIANATUL KHOIRIYAH; Ita Fauziyah; Zaenal Mustakim; Rahmat Kamal (MGMP PAI SMP BINTAN, 2025)
This study aims to analyze the management of Islamic education planning at MI Salafiyah Karangjompo, Tirto, Pekalongan. The research focuses on how planning processes are implemented and managed to improve the quality of Islamic education in elementary Islamic institutions. The study employs a qualitative descriptive approach using observation, interviews, and documentation as data collection techniques. The findings indicate that Islamic education planning at MI Salafiyah Karangjompo follows systematic stages, including needs analysis, goal formulation, policy setting, program implementation, and evaluation. Teachers actively design lesson plans, integrate Islamic values into learning, and align objectives with the institution’s vision. Effective educational planning contributes significantly to improving school management performance and fostering students’ Islamic character.